Investigation of methylotrophic yeasts expression systems for the production of self-assembling proteins with biological applications - Bredell, Wilhelmina Jacoba (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.